2004
DOI: 10.1161/01.res.0000122044.21787.01
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxation by Red Blood Cells and Impairment in Diabetes

Abstract: Abstract-Vascular dysfunction in diabetes is attributed to lack of bioavailable nitric oxide (NO) and is postulated as a primary cause of small vessel complications as a result of poor glycemic control. Although it has been proposed that NO is bound by red blood cells (RBCs) and can induce relaxation of blood vessels distal to its site of production in the normal circulation, the effect of RBC glycation on NO binding and relaxation of hypoxic vessels is unknown. We confirm RBC-induced vessel relaxation is inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 49 publications
1
59
0
1
Order By: Relevance
“…These data are in contrast to previous studies showing vasodilatory effects of RBCs added to rabbit aortic preparations under hypoxic conditions. 39,43 To directly compare our results with those of these studies, nitrite-free RBCs were added to hypoxic rabbit thoracic aorta preparations. Interestingly, using this vascular preparation, RBCs alone induced an initial and brief 10% relaxation that was followed by vasoconstriction ( Figure 5B).…”
Section: Hypoxic Vasodilation Mediated By Rbcs Occurs Through Nitritementioning
confidence: 96%
See 1 more Smart Citation
“…These data are in contrast to previous studies showing vasodilatory effects of RBCs added to rabbit aortic preparations under hypoxic conditions. 39,43 To directly compare our results with those of these studies, nitrite-free RBCs were added to hypoxic rabbit thoracic aorta preparations. Interestingly, using this vascular preparation, RBCs alone induced an initial and brief 10% relaxation that was followed by vasoconstriction ( Figure 5B).…”
Section: Hypoxic Vasodilation Mediated By Rbcs Occurs Through Nitritementioning
confidence: 96%
“…Previous studies have shown a vasodilatory effect of RBCs added to rabbit thoracic aorta at low oxygen tensions (approximately 10 mmHg), 39,43 a response that has been interpreted in favor of the hypothesis that SNOHb is a modulator of hypoxic vasodilation. However, deoxygenation of RBCs also results in ATP release, which stimulates vasodilation by activation of P 2Y (purinergic) receptors and eNOS.…”
Section: Hypoxic Vasodilation Mediated By Rbcs Occurs Through Nitritementioning
confidence: 99%
“…However, hemoglobin deoxygenation-based mechanisms may have a role in preventing tissue from moderate or severe hypoxia during intense metabolic stress. It was shown recently that the blood flow response in the heart and the diameter response of isolated thoracic aorta from the rabbit or mouse during severe hypoxia depend on O 2 -dependent delivery and release of NO from hemoglobin (Datta et al, 2004;Diesen et al, 2008;James et al, 2004).…”
Section: Hemoglobin Deoxygenation Does Not Regulate the Blood Flow Rementioning
confidence: 99%
“…In the R-state, SNO-Hb remains relatively unreactive but upon deoxygenation, T-state SNO-Hb can rapidly react with thiols [GSH or anion exchanger-1 (AE-1) thiols] and transmit a vasodilatory signal out of the RBC (suppl Fig 1) 8-12 . This hypothesis has been extended recently to suggest that dysfunction in this pathway leads to a variety of systemic vascular and pulmonary diseases and contributes to pathologic effects associated with diabetes, congestive heart failure and with transfusion of banked blood [13][14][15][16][17] . These pioneering studies also began to resolve a long standing question in hemoglobin biology, namely the role of the highly conserved β93Cys residue.…”
mentioning
confidence: 99%